KONSEP QUR’ANI DALAM PEMIKIRAN TASAWUF IBNU QAYIM AL-JAUZIYAH - Marhaban, Marhaban (At-Tibyan: Jurnal Ilmu Alqur'an dan Tafsir, 2018)
The attitude of seclusion from worldly life is absolute prerequisite for achieving a high spiritual experience. This is based on the fait that love of the excessive world will lead to contamination and destruction of spiritual originality on human psyche. It can notbe denied that being closer to God by understanding the Qur'an has implications for individual piety. Person who pursues or the life Sufism will have the experience of spirituality, with that attitude without any transformation into social life, then someone who lives the life of Sufism will be neglecting social life. The concept of Sufism taught by IbnQayyim Al-Jauziyah is that of health of soul.